Crystal structure of poly[[aqua(μ2-pyrazine-κ2N:N′)(μ2-2,3,5,6-tetrachlorobenzene-1,4-dicarboxylato-κ2O1:O4)copper(II)] hemihydrate] - Hitoshi Kumagai; Satoshi Kawata; Nobuhiro Ogihara (Acta Crystallographica Section E: Crystallographic Communications)
The asymmetric unit of the title compound, {[Cu2(C8Cl4O4)2(C4H4N2)2(H2O)2]·H2O}n or {[Cu2(Cl4bdc)2(pyz)2(H2O)2]·H2O}n comprises of a CuII ion, one tetrachlorobenzenedicarboxylate ion (Cl4bdc2−), one pyrazine ligand (pyz), and one and a half water molecules. The CuII ion exhibits a five-coordinated square-pyramidal geometry with a CuN2O3 coordination environment comprising two oxygen atoms of the Cl4bdc2− ligands, one oxygen atom of a water molecule, and two nitrogen atoms of the pyz ligands. The carboxylate group is almost perpendicular to the benzene ring and shows monodentate coordination to the CuII ion. The CuII ions of these units are bridged by both the Cl4bdc2− and pyz ligands to form two-dimensional (2D) layers, which are linked by alternating hydrogen-bonding and C—Cl...π interactions to yield a three-dimensional network.